Extracurricular Management in the Development of Soft Skills For Students - Baharuddin, Muhtadin; Marisa, Riandi; Bahri, Saiful (EDUTEC : Journal of Education And Technology, 2024)
This study explores the management of extracurricular activities in developing students' soft skills at Khairu Ummah Islamic Boarding School. Using a qualitative research method with a phenomenological approach, the study aimed to understand how extracurricular activities contribute to soft skills development. The findings reveal that the school focuses on religion-based soft skills training, encompassing personal, social, and academic development. The goal is to equip students with the necessary skills to confidently navigate life beyond school, grounded in religious practices and strong morals. The extracurricular training is implemented in three stages: 1) Teaching, which integrates Islamic values into activities; 2) Habituation, which encourages students to adopt positive habits such as timely prayer and discipline; and 3) Assignments, providing students with opportunities to develop their soft skills through roles in various organizations, such as room administrators, rayon administrators, and scouting coordinators. These activities, including mandatory scouting and language development programs, are tailored to the specific life skills the school aims to foster.